Pericardial Manifestations in Inflammatory Bowel Disease: A Report of Two Cases. Issue 3 (20th November 2019) - Qazi, T; Christian, K E; Farraye, F A; Cross, R K
Abstract: Pericardial involvement in the setting of inflammatory bowel disease can occur not only as an adverse event related to medical therapy but also as an extraintestinal manifestation of the disease itself. In the following case series, we describe 2 cases of pericarditis in patients diagnosed with Crohn disease. Our first case reviews the clinical presentation of acute pericarditis as an adverse event associated with anti-tumor necrosis factor therapy. In contrast, our second patient is a case of acute pericarditis as a precursor of the clinical recurrence of Crohn disease following operative resection. Pericardial disease should be considered in the differential diagnosis of acute and subacute presentations of chest discomfort and shortness of breath in patients with inflammatory bowel disease. Lay Summary: Herein, we present 2 cases of inflammatory bowel disease (IBD) effecting the heart. In the first case, the patient developed inflammation of the heart due to medication and in the second case the patient developed inflammation due to IBD.